Author Correction: Comprehensive comparative analysis of 5′-end RNA-sequencing methods. (December 2018) - Adiconis, Xian; Haber, Adam; Simmons, Sean; Moonshine, Ami; Ji, Zhe; Busby, Michele; Shi, Xi; Jacques, Justin; Lancaster, Madeline; Pan, Jen; Regev, Aviv; Levin, Joshua
The original version of this paper contained an incorrect primer sequence. In the Methods subsection "Rampage libraries, " the text for modification 3 stated that the reverse primer used for library indexing was 5′-CAAGCAGAAGACGGCATACGAGATXXXXXXXXGTGACTGGAGT-3′. The correct sequence of the oligonucleotide used is 5′-CAAGCAGAAGACGGCATACGAGATXXXXXXXXGTGACTGGAGTTCAGACGTGTGCTCTTCCGATCT-3′. This error has been corrected in the PDF and HTML versions of the paper.